Heterologous expression of human norovirus GII.4 VP1 leads to assembly of T=4 virus-like particles - Devant, Jessica; Hofhaus, Götz; Bhella, David; Hansman, Grant S. (Antiviral research, 2019)
Human noroviruses are a leading cause of acute gastroenteritis, yet there are still no vaccines or antivirals available. Expression of the norovirus capsid protein (VP1) in insect cells typically results in the formation of virus-like particles (VLPs) that are morphologically and antigenically comparable to native virions. Indeed, several different norovirus VLP candidates are currently used in clinical trials. So far, structural analysis of norovirus VLPs showed that the capsid has a T=3 icosahedral symmetry and is composed of 180 copies of VP1 that are folded into three quasi-equivalent subunits (A, B, and C). In this study, the VLP structures of two norovirus GII.4 genetic variants that were identified in 1974 and 2012 were determined using cryo-EM. Surprisingly, we found that greater than 95% of these GII.4 VLPs were larger than virions and 3D reconstruction showed that these VLPs exhibited T=4 icosahedral symmetry. We also discovered that the T=4 VLPs presented several novel structural features. The T=4 particles assembled from 240 copies of VP1 that adopted four quasi-equivalent conformations (A, B, C, and D) and formed two distinct dimers, A/B and C/D. The protruding domains were elevated ∼21Å off the capsid shell, which was ∼7Å more than in the previously studied GII.10 T=3 VLPs. A small cavity and flap-like structure at the icosahedral two-fold axis disrupted the contiguous T=4 shell. Overall, our findings indicated that GII.4 VP1 sequences assemble into T=4 VLPs and these larger particles might have important consequences for VLP-based vaccine development.
Gesehen am 06.12.2021